THE EFFECT OF SALES PROMOTION AND HEDONIC SHOPPING ON IMPULSE BUYING ON THE MARKETPLACE SHOPEE (Case Study In Tambakrigadung Community, Lamongan Regency) - Bella Maulina; Nurul Badriyah; Yuhronur Efendi (Jurnal Scientia, 2022)
Additionally, this study aims to determine the effect of sales promotion and hedonic shopping on impulse buying on the Shopee marketplace in the Tambakrigadung community, Lamongan district. The data analysis technique method used is validity test, reliability, normality, multicollinearity, heteroscedasticity, auto correlation, multiple linear regression analysis, t test, f test, coefficient of determination (R2), multiple correlation. Meanwhile, the results of this study indicate that:1) Sales Promotion partially has no significant effect on Impulse Buying on the Shopee marketplace, while Hedonic Shopping has a significant effect on Impulse Buying on the Shopee marketplace.2) Sales Promotion and Hedonic Shopping simultaneously affect Impulse Buying on the Shopee marketplace.3) Hedonic Shopping is the variable with the most dominant influence on Impulse Buying. It’s proven from the multiple linear regression calculation of the hypothesis = 6.665 + (-0.188) X1 + 0.947 X2.